MicroRNA-712 restrains macrophage pro-inflammatory responses by targeting LRRK2 leading to restoration of insulin stimulated glucose uptake by myoblasts. (February 2017) - Talari, Malathi; Nayak, Tapan Kumar Singh; Kain, Vasundhara; Babu, Phanithi Prakash; Misra, Parimal; Parsa, Kishore V.L.
Highlights: MicroRNA-712 levels are significantly down-regulated in inflamed macrophages. Forced expression of miR-712 reduced pro-inflammatory responses of macrophages. miR-712 targets 3′ UTR of LRRK2. Over-expression of miR-712 in macrophages blocked their paracrine effects on insulin sensitivity. Restoration of miR-712 expression may ameliorate inflammation induced insulin resistance. Abstract: Chronic inflammatory diseases such as insulin resistance, Type 2 diabetes, neurodegenerative diseases etc., are shown to be caused due to imbalanced activation states of macrophages. MicroRNAs which are transcriptional/post-transcriptional regulators of gene expression drive several pathophysiological processes including macrophage polarization. However the functional role of microRNAs in regulating inflammation induced insulin resistance is ill defined. In our current study we observed that the expression of miR-712 was reduced in macrophages exposed to LPS and IFN-γ. Ectopic expression of miR-712 in RAW 264.7 mouse macrophages impaired the expression of iNOS protein and secretion of pro-inflammatory cytokines such as TNF-α, IL-6 and IFN-β which in turn led to improved insulin stimulated glucose uptake in co-cultured L6 myoblasts. Mechanistically, we identified that miR-712 targets the 3′UTR of a potent inflammatory gene LRRK2 and dampens the phosphorylation of p38 and ERK1/2 kinases. Taken together, our data underscore the regulatory role of miR-712 in restoring insulin stimulated glucose uptake by myoblasts through down-regulating macrophage mediated inflammatory responses.